Development of Mutants in Sugarcane through Callus Culture - Mahmud, Kuasha; Nasiruddin, KM; Hossain, MA; Hassan, L (Plant Tissue Culture and Biotechnology, 2016)
The effects of different concentrations (0.0 M, 0.01 M, 0.02 M and 0.03 M for 24 hours treatment) of chemical mutagen like, ethyl methanesulfphonate (EMS) on callus derived from sugarcane var. Isd 37, Isd 39 and Isd 40 were investigated for in vitro plant regeneration. The highest number of shoots (58.33%) was reduced over control of Isd 40 followed by Isd 37 (57.62%) and Isd 39 (the lowest 56.06%), respectively due to the use of EMS for treating calli. The regeneration of mutant plantlets was achieved from EMS (0.01 M) treated calli obtained from leaf sheath explants on MS supplemented with 2, 4?D (3 mg/l) and 10% coconut water. Most of the mutant plants were developed from Isd 37. The developed mutant plants showed variation in tiller number, internode, green leaf, millable cane and stalk colour from the source variety of Isd 37. Plant Tissue Cult. & Biotech. 26(1): 123-130, 2016 (June)